Modified alumina carrier as well as preparation method and application thereof
By using potassium salt for precipitation and modification in the preparation process of alumina support, combined with hydrothermal crystallization method, the problems of poor crystallinity and pore distribution of the support are solved, the desulfurization performance and stability of the catalyst are improved, and the goals of environmentally friendly production and efficient desulfurization are achieved.
Patent Information
- Application Number
- CN202311390700.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-25
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-10-25
AI Technical Summary
In the prior art, the crystal form of the alumina support is incomplete, the pore size distribution is not concentrated, and the crystallinity is low, resulting in low desulfurization activity and selectivity of the catalyst, and the modification additive is prone to loss, making it difficult to maintain the stability of the catalyst for a long time.
By using potassium salt as a precipitant and a modified metal additive precursor, the purpose of precipitation and metal additive modification is achieved simultaneously. Combined with the hydrothermal crystallization method of co-precipitated slurry, a modified alumina carrier with concentrated pore distribution and high crystallinity was prepared.
It achieves higher desulfurization selectivity and activity of the catalyst, avoids the loss of modification additives, simplifies the production process, reduces the generation of waste liquid, and meets the needs of national VI standard clean gasoline quality upgrade.
Smart Images

Figure CN119869529A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrodesulfurization catalysis, and in particular to a modified alumina carrier and a preparation method and application thereof. Background Art
[0002] The desulfurization activity and selectivity of the highly selective hydrodesulfurization catalyst for catalytic cracking gasoline are closely related to the stacking layer number and platelet size of the MoS2 active phase, while the pore structure and pore size distribution also determine the mass transfer efficiency of sulfides and olefins in the catalyst system and affect the hydrogenation selectivity. By introducing additives such as rare earth elements and alkali metal elements (such as K and Mg) to modify the carrier, or using alumina with high crystallinity and less surface hydroxyl groups as a carrier, the stacking layer number, platelet length and pore structure of the MoS2 active phase can be effectively regulated, which is beneficial to improve the metal sulfidation degree, improve the desulfurization selectivity, inhibit olefin saturation, and reduce octane number loss.
[0003] At present, the modification method of carrier additives often adopts the loading method, which generally needs to be loaded on the catalyst carrier by one or two impregnations. The preparation process is cumbersome and costly, and it is easy to cause the modified additives to accumulate on the carrier surface and difficult to enter the catalyst pores, affecting the control effect of the modified additives on the metal active phase, resulting in low desulfurization activity and selectivity. At the same time, it is easy to lose during use, and it is difficult to maintain the stability of the catalyst for a long time. The method of introducing the modified additive in the synthesis of pseudo-boehmite by co-precipitation, because K is mainly added as a precipitant, in order to control the precipitant metal cation K + The content of MoS2 requires multiple washings, resulting in a large amount of waste liquid, which is not conducive to environmental protection. At the same time, the crystal phase structure of alumina is also one of the key factors affecting the performance of hydrodesulfurization catalysts. Conventional alumina has irregular crystal structure, low crystallinity, few surface hydroxyls, and non-concentrated pore size distribution, which has low mass transfer rates for reactants and products. This can easily lead to enhanced interaction between the carrier and the active metal component, which is not conducive to the formation of MoS2 active phase and affects the desulfurization activity and selectivity of the catalyst. The synthesis of alumina with concentrated pore distribution and high crystallinity is difficult.
[0004] Therefore, it is of great significance to study and develop an alumina carrier with both concentrated pore distribution and high crystallinity. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of incomplete crystal form, unconcentrated pore size distribution, low crystallinity, etc. of the modified alumina carrier in the prior art, and to provide a modified alumina carrier with concentrated pore distribution and high crystallinity and a preparation method thereof.
[0006] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a modified alumina carrier, wherein the modified alumina carrier comprises silicon oxide, potassium oxide, zirconium oxide, lanthanum oxide, copper oxide and aluminum oxide; wherein the volume percentage of pore volume with a pore diameter of 13-23nm accounts for 63-85% of the total pore volume, and the relative crystallinity is not less than 95%.
[0007] A second aspect of the present invention provides a method for preparing a modified alumina carrier, comprising the following steps:
[0008] (1) subjecting an alkaline precipitant solution, an aluminum salt solution and a modified metal salt solution to a precipitation reaction, and subjecting the obtained product to an aging reaction;
[0009] (2) subjecting the slurry obtained in step (1) to a hydrothermal crystallization reaction with a structure directing agent and filtering;
[0010] (3) The filter cake obtained by filtering in step (2) is molded with a binder, a pore-enlarging agent and an extrusion aid to obtain a modified alumina carrier.
[0011] The third aspect of the present invention provides a hydrodesulfurization catalyst, wherein the catalyst comprises a carrier and an active component A and an active component B supported on the carrier, and the carrier is selected from the carrier described in the first aspect or the carrier prepared by the method described in the second aspect;
[0012] Wherein, the active component A is cobalt oxide and / or nickel oxide; the active component B is molybdenum oxide;
[0013] Wherein, based on the total weight of the catalyst, the content of the active component A is 1-4wt%, the content of the active component B is 8-16wt%, and the content of the carrier is 80-91wt%.
[0014] The fourth aspect of the present invention provides an application of the catalyst described in the third aspect in the selective hydrodesulfurization of catalytic cracking gasoline.
[0015] The fifth aspect of the present invention provides a method for selective hydrodesulfurization of catalytic cracking gasoline, the method comprising: subjecting the catalyst described in the third aspect to sulfurization treatment, and contacting the obtained presulfurized catalyst with catalytic cracking gasoline to carry out selective hydrodesulfurization reaction.
[0016] Through the above technical solution, the present invention mainly has the following beneficial effects:
[0017] (1) The modified alumina carrier provided by the present invention has a more complete crystal structure, wherein the volume percentage of pores with a pore size of 13-23 nm to the total pore volume is 63-85%, and the relative crystallinity is not less than 95%. The concentrated pore structure is conducive to improving the mass transfer efficiency of sulfide molecules and olefin molecules in the catalyst system and improving the desulfurization selectivity of the catalyst; the relative crystallinity is not less than 95%, which is conducive to making the alumina crystal more complete and generating more metal additive-O-Al bonds, reducing the number of surface hydroxyl groups, promoting the entry of modified additives into the carrier pores, helping to weaken the interaction between the carrier and the active metal component, and promoting the formation of MoS2 active phase.
[0018] (2) The preparation method of the modified alumina carrier provided by the present invention uses potassium salt as both a precipitant and a modified metal additive precursor, and the purpose of precipitation and metal additive modification is achieved simultaneously. The potassium salt is used as a precipitant to ensure that the aluminum hydroxide grains are uniform, the structure is complete, and there is little agglomeration; at the same time, the potassium salt is used as a modified metal additive precursor. Through the in-situ modification of the potassium salt, it has a concentrated pore structure (the volume percentage of pores with a pore size of 13-23nm accounts for 63-85% of the total pore volume), which helps to improve the desulfurization selectivity.
[0019] (3) The preparation method of the modified alumina carrier provided by the present invention is adopted. By first precipitating aluminum salt and then precipitating the auxiliary metal, the rich pore structure of alumina is utilized to achieve in-situ modification of alumina with the auxiliary agent, thereby prompting the metal auxiliary agent to enter the alumina pores, effectively adjusting the interaction force between the metal and the carrier, avoiding problems such as auxiliary agent loss during use, and at the same time improving the sulfidation degree of the active metal component, increasing the number of MoS2 active centers, and helping to improve the desulfurization activity.
[0020] (4) The preparation method of the modified alumina carrier provided by the present invention is adopted. The modified alumina dry gel prepared by the present invention is added to the aged slurry as a structure directing agent, and hydrothermal crystallization is carried out in a high-pressure reactor. The crystal phase structure of the structure directing agent is used to promote the regular formation and growth of crystal nuclei, thereby improving the crystallinity and crystal structure integrity of the modified alumina and the formation of metal additive-O-Al bonds, reducing the number of surface hydroxyl groups, and promoting the entry of the modified additive into the carrier pores, which helps to weaken the interaction between the carrier and the active metal component and promote the formation of the MoS2 active phase.
[0021] (5) By adopting the preparation method of the modified alumina carrier provided by the present invention, the filter cake does not need to be washed multiple times to remove the precipitant metal cations, and can be directly dried to obtain the modified alumina dry gel, thereby simplifying the production process and avoiding the problem of the precipitant metal cations needing to be washed multiple times in the conventional co-precipitation production process, resulting in a large amount of waste liquid, thereby achieving environmentally friendly production; at the same time, the filtrate can be recycled, and the solution obtained after filtration is used as a solvent for dissolving aluminum salt and alkaline precipitant, and the modified auxiliary agent is dissolved in deionized water. The pH value of the precipitant solution is adjusted to meet the required pH value environment in the precipitation process, thereby achieving sufficient precipitation and solving the problem that the filtrate cannot be recycled due to the inability of the metal auxiliary agent to dissolve in the filtrate during the precipitation process. At the same time, the environmentally friendly production goal of zero discharge of waste liquid containing metal ions is achieved.
[0022] (6) The content of potassium oxide in the hydrodesulfurization catalyst prepared by using the modified alumina carrier provided by the present invention remains basically unchanged before and after the use of the catalyst, indicating that there is no loss of the potassium additive during the use of the catalyst provided by the present invention. This is mainly because the method provided by the present invention introduces the potassium additive during the preparation of the modified alumina carrier, which is more conducive to the entry of the potassium additive into the alumina pores, avoiding the problem that the modified additive of the conventional catalyst is easily accumulated on the carrier surface and difficult to enter the catalyst pores, and the modified additive is easily lost during the use of the catalyst, which helps to maintain the long-term stability of the catalyst.
[0023] (7) The hydrodesulfurization catalyst prepared using the modified alumina carrier provided by the present invention has a catalytic desulfurization rate of heavy gasoline of not less than 90% and a desulfurization selectivity of not less than 70%. Compared with the conventional catalyst preparation method, while achieving zero waste liquid discharge, the catalyst has a more concentrated pore structure and a higher desulfurization rate and desulfurization selectivity, meeting the requirements of deep desulfurization and reducing octane number loss during the quality upgrade of clean gasoline to the National VI standard. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the XRD spectrum of the modified alumina support prepared in Example 2;
[0025] Figure 2 This is the XRD spectrum of the modified alumina support prepared in Comparative Example 1. DETAILED DESCRIPTION
[0026] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0027] The first aspect of the present invention provides a modified alumina carrier, wherein the modified alumina carrier comprises silicon oxide, potassium oxide, zirconium oxide, lanthanum oxide, copper oxide and aluminum oxide; wherein the volume percentage of pore volume with a pore diameter of 13-23 nm accounts for 63-85% of the total pore volume, and the relative crystallinity is not less than 95%.
[0028] In the present invention, the volume percentage of the pore volume of the modified alumina carrier with a pore diameter of 13-23nm accounts for 63-85% of the total pore volume, and it has a concentrated pore structure, which improves the mass transfer efficiency of sulfide molecules and olefin molecules in the catalyst system, and helps to improve the desulfurization selectivity; the modified alumina carrier has a high crystallinity, and the relative crystallinity is not less than 95%, which is conducive to making the alumina crystal more complete and generating more metal additive-O-Al bonds, reducing the number of surface hydroxyl groups, and can effectively improve the catalyst hydrodesulfurization activity and selectivity.
[0029] In the present invention, the crystallinity of the modified alumina carrier is determined by characterizing the sample using a SmartLab X-ray diffractometer of Rigaku Corporation of Japan. The test conditions are: Cu-Kα radiation source; working current and voltage are 30mA and 40kV respectively; one-dimensional detector is used; 2θ angle is between 5°-80°, scanning speed is 10° / min, and step length is 0.05°. The relative crystallinity is calculated as follows:
[0030] Numerous literature research results show that in the X-ray diffraction spectrum, typical γ-Al2O3 characteristic diffraction peaks appear at 2θ=36.8°, 46.4° and 67.0°, corresponding to the (311), (400) and (440) crystal planes of γ-Al2O3, respectively.
[0031] Taking industrial alumina as the benchmark, the relative crystallinity calculation formula is:
[0032]
[0033] According to the present invention, the specific surface area of the modified alumina carrier is 230-260m 2 / g, the pore volume is 0.5-1.1mL / g, and the average pore diameter is 12-22nm.
[0034] In the present invention, the specific surface area, pore volume and average pore size of the modified alumina carrier and catalyst are characterized by an American Micrometeritics ASAP 2010 automatic adsorption instrument. The specific surface area is measured by a five-point BET method, and the pore distribution of the sample is measured by a BJH method. The sample is treated at 350°C for 4 hours, and then an adsorption-desorption experiment is performed at -196°C with N2 as the adsorbent.
[0035] Furthermore, the specific surface area of the modified alumina carrier is 233-255m 2 / g, the pore volume is 0.6-1mL / g, and the average pore diameter is 13-18nm.
[0036] Furthermore, the volume percentage of pores with a pore diameter of 14-19 nm to the total pore volume is 60-80%, and the relative crystallinity is not less than 95%.
[0037] In the present invention, the pore size is further narrowed (from 13-23 nm to 14-19 nm), and the range of the volume percentage of the pore volume of the narrowed pore size to the total pore volume is also narrowed accordingly.
[0038] According to the present invention, based on the total weight of the modified alumina carrier, the content of silicon oxide is 0.1-1.5wt%, the content of potassium oxide is 2-4.5wt%, the content of zirconium oxide is 0.1-2.3wt%, the content of lanthanum oxide is 0.1-1.3wt%, the content of copper oxide is 0.1-2.3wt%, and the content of aluminum oxide is 88.1-97.6wt%;
[0039] Preferably, based on the total weight of the modified alumina carrier, the content of silicon oxide is 0.5-1.1wt%, the content of potassium oxide is 2.5-4.1wt%, the content of zirconium oxide is 0.5-1.5wt%, the content of lanthanum oxide is 0.3-0.8wt%, the content of copper oxide is 0.3-0.8wt%, and the content of aluminum oxide is 91.7-95.9wt%.
[0040] In the present invention, silicon oxide is introduced into the carrier to improve the acidity of the carrier; potassium oxide is introduced to have an electron-donating effect, and the characteristic of potassium as an alkaline modification aid is utilized to change the acidity distribution of the carrier and improve the selectivity of the catalyst; zirconium oxide, lanthanum oxide and copper oxide are introduced to further prepare the catalyst, and Co / Ni can be replaced from the tetrahedral active sites, thereby improving the interaction force between the modified alumina carrier and the active components, which is beneficial to the formation of the MoS2 active phase, and the low-temperature desulfurization performance is enhanced, which is more beneficial to deep desulfurization while reducing olefin saturation, and improving the activity and selectivity of the catalyst for hydrodesulfurization.
[0041] A second aspect of the present invention provides a method for preparing a modified alumina carrier, comprising the following steps:
[0042] (1) subjecting an alkaline precipitant solution, an aluminum salt solution and a modified metal salt solution to a precipitation reaction, and subjecting the obtained product to an aging reaction;
[0043] (2) subjecting the slurry obtained in step (1) to a hydrothermal crystallization reaction with a structure directing agent and filtering;
[0044] (3) The filter cake obtained by filtering in step (2) is molded with a binder, a pore-enlarging agent and an extrusion aid to obtain a modified alumina carrier.
[0045] In the present invention, potassium salt is used as both a precipitant and a modified metal additive precursor, so as to achieve the purpose of precipitation and metal additive modification simultaneously. Combined with the method of hydrothermal crystallization of coprecipitation slurry, a modified alumina carrier with concentrated pore distribution is obtained, which further improves the crystallinity of the modified alumina carrier, promotes the integrity of the crystal structure and the formation of metal additive-O-Al bonds, reduces the number of surface hydroxyl groups, and promotes the entry of the modified additive into the carrier pores, which helps to weaken the interaction between the carrier and the active metal component and promotes the formation of MoS2 active phase; and the coprecipitation mother liquor recycling method is used to effectively improve the catalyst hydrodesulfurization activity and selectivity, while achieving the environmentally friendly production goal of zero waste liquid discharge, meeting the needs of deep desulfurization and reducing octane number loss during the quality upgrade of clean gasoline of National VI standard.
[0046] According to the present invention, the alkaline precipitant solution in step (1) comprises an alkaline precipitant, and the alkaline precipitant is selected from one or more of potassium carbonate, potassium hydroxide and potassium bicarbonate;
[0047] and / or, the aluminum salt solution comprises a soluble aluminum salt, and the soluble aluminum salt is selected from aluminum nitrate and / or aluminum sulfate;
[0048] And / or, the modified metal salt solution contains a modified metal salt, and the modified metal salt is selected from one or more of zirconium nitrate, zirconium nitrate, copper nitrate, zirconium acetate, lanthanum acetate, and copper acetate.
[0049] In the present invention, the pH of the alkaline precipitant solution is 8-12, preferably 10-12.
[0050] In the present invention, the pH of the solution is adjusted by adding an inorganic base or an organic base, wherein the inorganic base is selected from at least one of ammonia water, ammonium bicarbonate and ammonium carbonate, and the organic base is selected from carbonamide and / or triethylamine. The inventors of the present invention have found in their research that the pH of the alkaline precipitant will affect the grain morphology, grain size and crystallinity. If the pH value is too high, the grains will be larger and the crystal form will be irregular. If the pH value is too low, the precipitation will be incomplete and an amorphous structure will exist, and the grains will be smaller and easy to accumulate. In Examples 1-3 of the present invention, the effects of different pH values on the crystallinity of modified alumina dry gel are compared. As the pH value gradually increases, the crystallinity first increases and then decreases.
[0051] In the present invention, potassium salt is used as both a precipitant and a modified metal auxiliary agent precursor, achieving the purpose of precipitation and metal auxiliary agent modification simultaneously. Potassium salt as a precipitant ensures that the aluminum hydroxide crystals are uniform, the structure is complete, and there is less agglomeration; at the same time, potassium salt is used as a modified metal auxiliary agent precursor, and through the in-situ modification of potassium salt, it has a concentrated pore structure (the volume percentage of pores with a pore diameter of 13-23nm accounts for 63-85% of the total pore volume), which helps to improve the desulfurization selectivity.
[0052] In the present invention, the modified metal salt is selected from metal salts of zirconium, lanthanum and copper, wherein the mass ratio of the zirconium, lanthanum and copper metal salts is 0.28-6.34:0.27-3.46:0.30-7.00. The introduction of zirconium oxide, lanthanum oxide and copper oxide into the alumina carrier can replace Co / Ni from the tetrahedral active sites, improve the interaction between the modified alumina carrier and the active components, and is beneficial to the formation of the MoS2 active phase. The low-temperature desulfurization performance is enhanced, which is more conducive to deep desulfurization while reducing olefin saturation, thereby improving the activity and selectivity of the catalyst for hydrodesulfurization.
[0053] According to the present invention, the precipitation reaction in step (1) includes a first precipitation reaction of an alkaline precipitant solution with an aluminum salt solution and a second precipitation reaction of an alkaline precipitant solution with a modified metal salt solution.
[0054] By first precipitating aluminum salts and then precipitating additive metals, the rich pore structure of alumina is utilized to achieve in-situ modification of alumina with additives, prompting the metal additives to enter the alumina pores, effectively adjusting the interaction between the metal and the carrier, and avoiding problems such as additive loss during use. At the same time, the sulfidation degree of active metal components is improved, and the number of MoS2 active centers is increased, which helps to improve desulfurization activity.
[0055] The inventors of the present invention have found in their research that the prior art usually uses a spraying method or an impregnation method to load modified metals on an already synthesized alumina carrier. These methods easily lead to the accumulation of modified additives on the carrier surface and difficulty in entering the pores, further leading to the agglomeration of metal additives on the surface of the crystal nucleus, weak interaction between the metal and the carrier, and easy loss during use. However, by using the method provided by the present invention, the modified metal is introduced during the preparation of the alumina carrier, and the in-situ modification of the additive to the alumina is achieved through a two-step precipitation reaction, and the metal additive is enabled to enter the pores of the alumina. Compared with the prior art, the method of the present invention is more conducive to regulating the interaction between the metal and the carrier, and avoiding the loss of the additive during use. In Examples 1-12 of the present invention, the potassium content of the catalyst remains basically unchanged before and after use, which fully illustrates that there is no problem of potassium loss during the use of the catalyst developed by the present invention, and further illustrates that the catalyst carrier and the metal active component have a suitable interaction force.
[0056] According to the present invention, the conditions of the first precipitation reaction include: reaction temperature of 20-80°C, pH of 7-9, and reaction time of 30-50min; preferably, reaction temperature of 50-70°C, pH of 8-9, and reaction time of 30-40min;
[0057] According to the present invention, the conditions of the second precipitation reaction include: reaction temperature of 20-80°C, pH of 7-9, and reaction time of 3-10 min; preferably, reaction temperature of 50-70°C, pH of 8-9, and reaction time of 5-8 min.
[0058] In the present invention, the alkaline precipitant solution and the aluminum salt solution are first added to the reactor in parallel and reacted under the first precipitation reaction condition. After the aluminum salt solution is added, the alkaline precipitant solution and the modified metal salt solution are continued to be added to the reactor in parallel and reacted under the second precipitation reaction condition. Such an addition sequence is conducive to the modified metal entering the carrier pore channel, better modifying the carrier pore structure and acid distribution, having a concentrated pore structure, and the volume percentage of the pore volume with a pore diameter of 13-23nm to the total pore volume is 63-85%.
[0059] In the present invention, the method for adjusting the pH of the first precipitation reaction and the second precipitation reaction is to control the drop rate of the alkaline precipitant. In the preferred pH range of the present invention, it is avoided that the pH value is too high, resulting in large grains and irregular crystal forms, and the pH value is too low, resulting in incomplete precipitation, amorphous structure, small grains and easy accumulation.
[0060] In the present invention, the conditions of the aging reaction in step (1) include: an aging temperature of 60-100° C. and an aging time of 60-180 min; preferably, the aging temperature is 60-70° C. and the aging time is 100-150 min.
[0061] According to the present invention, the structure directing agent in step (2) is a modified alumina dry glue.
[0062] In the present invention, the modified alumina dry glue can be self-made or selected from the filter cake described in step (3), and the added amount of the structure directing agent accounts for 1-10% of the total mass of the filter cake after filtration, preferably 3-6%.
[0063] In the present invention, the preparation method of the structure directing agent is as follows:
[0064] Weigh 374g of aluminum nitrate nonahydrate and dissolve it in deionized water, make the volume to 1L, and the solution concentration is Al2O351g / L; weigh 706g of potassium carbonate and dissolve it in deionized water, add 41.7g of urea, and use the filtrate to make the volume to 4L, the solution concentration is K2O125g / L, and the solution pH is 9.5, as a precipitant; weigh 2.3g of zirconium nitrate, 0.97g of lanthanum nitrate, and 1.1g of copper nitrate and dissolve them in 60g of deionized water to prepare a modification auxiliary agent solution.
[0065] First, add deionized water to the reactor, preheat it to 60°C, add 1L aluminum nitrate solution and 1.5L potassium carbonate solution in parallel under stirring, adjust the flow rate of solution addition, control the pH value of the slurry in the reactor to 7, and add the feed time for 40min; after the addition is completed, continue to add the mixed modification auxiliary solution of zirconium nitrate and lanthanum nitrate and 152mL potassium carbonate solution in parallel under stirring, adjust the flow rate of solution addition, and add the feed time for 5min; after the addition is completed, stand and age for 120min at this temperature and pH value. After the aging is completed, filter and dry the obtained filter cake at 150°C for 120min to obtain a structure directing agent, and the filtrate can be recycled as a solvent for the aluminum salt solution and the alkaline precipitant solution.
[0066] According to the present invention, the mass ratio of the structure directing agent to the slurry is 0.0012-0.0046:1.
[0067] In the present invention, a structure directing agent is added in step (2), and the structure directing agent is used to promote the directional and regular formation and growth of the modified alumina crystal nuclei by utilizing the structural characteristics of concentrated pore distribution and complete crystal form, so that the crystal form of the modified alumina carrier is complete and the crystallinity of the modified alumina carrier is improved.
[0068] According to the present invention, the conditions of the hydrothermal crystallization reaction in step (2) include: a reaction temperature of 120-180° C., a reaction time of 120-600 min;
[0069] Preferably, the reaction temperature is 130-160° C., and the reaction time is 180-360 min.
[0070] If the reaction temperature of hydrothermal crystallization is too high, the intensity of the alumina diffraction peak will decrease, the grains will be larger, and the specific surface area will be reduced, which is not conducive to the dispersion of active metal components; if the reaction temperature of hydrothermal crystallization is too low, the alumina crystal form will be incomplete and the degree of crystallinity will be low; the modified alumina carrier prepared under the above hydrothermal crystallization conditions has a complete crystal structure and a concentrated pore structure, which helps to improve the desulfurization activity and selectivity of the catalyst.
[0071] In the present invention, the modified alumina dry glue prepared by the present invention is added to the aged slurry as a structure directing agent, and hydrothermal crystallization is carried out in a high-pressure reactor. The crystal phase structure of the structure directing agent is utilized to promote the regular formation and growth of crystal nuclei, thereby improving the crystallinity and crystal structure integrity of the modified alumina and the formation of metal additive-O-Al bonds, reducing the number of surface hydroxyl groups, and promoting the modified additive to enter the carrier pores, thereby helping to weaken the interaction force between the carrier and the active metal component and promoting the formation of the MoS2 active phase.
[0072] In the present invention, the filtrate obtained by filtration in step (2) can be reused as the solvent for the aluminum salt solution and the alkaline precipitant solution in step (1).
[0073] In the present invention, the filter cake obtained by filtration in step (2) does not need to be washed multiple times, but is directly dried, and the dried filter cake enters step (3). The drying conditions include: drying temperature of 120-180°C, drying time of 60-120 minutes; preferably, drying temperature of 120-150°C, drying time of 90-120 minutes.
[0074] In the present invention, the filter cake does not need to be washed multiple times to remove the precipitant metal cations, which simplifies the production process and avoids the problem of a large amount of waste liquid caused by the need to wash the precipitant metal cations multiple times in the conventional co-precipitation production process. The operation steps are simpler, which is conducive to reducing energy consumption in the preparation process and achieving environmentally friendly production. At the same time, the filtrate can be recycled, and the solution obtained after filtration is used as a solvent for dissolving aluminum salt and alkaline precipitant. The modified auxiliary agent is dissolved in deionized water, and the pH value of the precipitant solution is adjusted to meet the pH value environment required in the precipitation process. While achieving sufficient precipitation, it solves the problem that the filtrate cannot be recycled due to the inability of the metal auxiliary agent to dissolve in the filtrate during the precipitation process, and at the same time achieves the environmentally friendly production goal of zero discharge of waste liquid containing metal ions.
[0075] According to the present invention, the binder in step (3) comprises silica sol and compound A, wherein the compound A is selected from one or more of nitric acid, acetic acid and malic acid;
[0076] And / or, the pore expanding agent is selected from one or more of citric acid, yeast, methyl cellulose, and hydroxypropyl methyl cellulose;
[0077] And / or, the extrusion aid is selected from one or more of sesbania powder, starch and citric acid.
[0078] According to the present invention, the mass ratio of the filter cake, the binder, the pore expander and the extrusion aid in step (3) is 1: 0.02-0.05: 0.01-0.1: 0.01-0.05. Within this addition range, the addition of an appropriate amount of the pore expander is conducive to obtaining a higher proportion of pores with a pore size of 14-19 nm.
[0079] According to the present invention, a modified alumina carrier is prepared according to the method described above.
[0080] The third aspect of the present invention provides a hydrodesulfurization catalyst, wherein the catalyst comprises a carrier and an active component A and an active component B supported on the carrier, and the carrier is selected from the carrier described in the first aspect or the carrier prepared by the method described in the second aspect;
[0081] Wherein, the active component A comprises cobalt oxide and / or nickel oxide; the active component B is molybdenum oxide;
[0082] Wherein, based on the total weight of the catalyst, the content of the active component A is 1-4wt%, the content of the active component B is 8-16wt%, and the content of the carrier is 80-91wt%.
[0083] In the present invention, based on the total weight of the catalyst, the content of the active component A is 2.5-3.5wt%, the content of the active component B is 10-13wt%, and the content of the carrier is 83.5-87.5wt%.
[0084] In the present invention, the bulk density of the catalyst is 0.5-0.8 g / mL, the pore volume is 0.3-0.8 mL / g, and the specific surface area is 150-300 m 2 / g, the average pore size is 8-18nm, and the volume percentage of pores with a pore size of 10-20nm accounts for 63-85% of the total pore volume.
[0085] Preferably, the catalyst has a bulk density of 0.6-0.7 g / mL, a pore volume of 0.4-0.6 mL / g, and a specific surface area of 170-225 m 2 / g, the average pore size is 9-15nm, and the volume percentage of pores with a pore size of 10-20nm accounts for 65-85% of the total pore volume.
[0086] The catalyst prepared by the invention has a concentrated pore structure, which improves the mass transfer efficiency of sulfide and olefin in the catalyst system and further improves the catalyst hydrogenation selectivity.
[0087] In the present invention, the preparation method of the hydrodesulfurization catalyst comprises:
[0088] (1) preparing a modified alumina carrier according to the method described in the second aspect;
[0089] (2) Impregnating equal volumes of the complex solution containing active component A and active component B on a modified alumina carrier, drying and calcining to obtain the hydrodesulfurization catalyst.
[0090] In the present invention, the metal salt of the active component A is selected from one or more of nitrates, basic carbonates, acetates or sulfates, preferably nitrates and / or basic carbonates. The metal salt of the active component B is selected from one or more of ammonium heptamolybdate, ammonium tetramolybdate, ammonium dimolybdate, and molybdenum oxide, preferably ammonium heptamolybdate and / or molybdenum oxide.
[0091] In the present invention, the complexing solution includes a composite complexing agent, which is selected from one or more of citric acid, phosphoric acid, tartaric acid, malic acid, oxalic acid, nitrilotriacetic acid, ethylenediaminetetraacetic acid and tetrahydroxypropylethylenediamine; the pH of the complexing solution is 0.1-5.
[0092] Preferably, the composite complexing agent is selected from one or more of citric acid and phosphoric acid, oxalic acid, and nitrilotriacetic acid; and the pH of the complexing solution is 1-3.
[0093] In the present invention, the equal volume impregnation is vacuum impregnation, and the conditions of the vacuum impregnation include: an impregnation pressure of 0.05-0.1 MPa, an impregnation time of 4-8 hours, and an impregnation temperature of 100-150°C.
[0094] Preferably, the impregnation pressure is 0.07-0.09 MPa, the impregnation time is 4-6 h, and the impregnation temperature is 100-120°C.
[0095] In the present invention, the drying conditions include: a drying temperature of 100-150° C. and a drying time of 3-6 hours; the roasting conditions include: a roasting temperature of 400-600° C. and a roasting time of 3-6 hours.
[0096] The fourth aspect of the present invention provides an application of the catalyst described in the third aspect in the selective hydrodesulfurization of catalytic cracking gasoline.
[0097] The fifth aspect of the present invention provides a method for selective hydrodesulfurization of catalytic cracking gasoline, the method comprising: presulfurizing the catalyst described in the third aspect, contacting the obtained presulfurized catalyst with catalytic cracking gasoline to carry out selective hydrodesulfurization reaction.
[0098] The presulfidation treatment is a conventional presulfidation treatment in the art. In a particularly preferred embodiment of the present invention, the presulfidation treatment process comprises: in the presence of hydrogen, bringing the sulfided oil and the sulfiding agent into contact with the catalyst to carry out a sulfidation reaction;
[0099] Among them, the volume space velocity of sulfurized oil is 1-3h -1 The volume ratio of hydrogen to sulfide oil is 100:1-500:1, and the sulfide pressure is 1-3MPa; the sulfide temperature is programmed heating, including: heating rate of 10-40℃ / h, staying at 150℃ for 2h, staying at 230℃ for 8h, and staying at 320℃ for 6h.
[0100] Preferably, the volume ratio of hydrogen to sulfide oil is 200:1-400:1, and the reaction pressure is 1-3 MPa; the temperature control is programmed heating, including: a heating rate of 20-30°C / h, staying at 150°C for 2h, staying at 230°C for 8h, and staying at 320°C for 6h.
[0101] According to the present invention, the conditions for the selective hydrodesulfurization of catalytic cracking gasoline include: reaction temperature 220-300°C, reaction pressure 1-3MPa, volume space velocity 1-4h -1 , hydrogen-oil volume ratio 100:1-500:1.
[0102] Preferably, the conditions for the selective hydrodesulfurization of catalytic cracking gasoline include: reaction temperature 220-300°C, reaction pressure 1-3MPa, volume space velocity 2-3h -1 , hydrogen-oil volume ratio 200:1-400:1.
[0103] In the present invention, the catalyst described in the third aspect is used as a selective hydrodesulfurization catalyst, the catalytic desulfurization rate of heavy gasoline is not less than 90%, and the desulfurization selectivity is not less than 70%. Compared with the conventional catalyst preparation method, while achieving zero discharge of waste liquid, the catalyst has a more concentrated pore structure and a higher desulfurization rate and desulfurization selectivity, meeting the needs of deep desulfurization and reducing octane number loss during the quality upgrading of clean gasoline of National VI standard.
[0104] The present invention will be described in detail below through examples.
[0105] In the following examples, the compositions of the modified alumina carrier and the catalyst were determined by X-ray fluorescence spectrometer;
[0106] The specific surface area, pore volume and average pore size of the modified alumina support and catalyst were characterized by an American Micrometeritics ASAP 2010 automatic adsorption instrument. The specific surface area was determined by the five-point BET method, and the pore distribution of the sample was measured by the BJH method. The sample was treated at 350°C for 4 hours, and then an adsorption-desorption experiment was performed at -196°C with N2 as the adsorbent.
[0107] The crystallinity of the modified alumina carrier was determined by characterizing the sample using a SmartLab X-ray diffractometer from Rigaku Corporation of Japan. The test conditions were: Cu-Kα radiation source; working current and voltage were 30 mA and 40 kV, respectively; one-dimensional detector; 2θ angle was between 5° and 80°, scanning speed was 10° / min, and step length was 0.05°. The relative crystallinity was calculated as follows:
[0108] The results of numerous literature studies show that in the X-ray diffraction spectrum, typical γ-Al2O3 characteristic diffraction peaks appear at 2θ=36.8°, 46.4° and 67.0°, corresponding to the (311), (400) and (440) crystal planes of γ-Al2O3, respectively. Based on industrial alumina, the relative crystallinity calculation formula is:
[0109]
[0110] In the following examples and comparative examples, the solvents of the aluminum salt solution and the alkaline precipitant solution are from the filtrate in the process of preparing the alkaline aluminum oxide dry gel, and the filtrate in all examples can be recycled.
[0111] Drugs and reagents were commercially available.
[0112] Preparation method of modified alumina dry glue: weigh 374g of aluminum nitrate nonahydrate and dissolve it in deionized water, make the volume to 1L, and the solution concentration is Al2O351g / L; weigh 706g of potassium carbonate and dissolve it in deionized water, add 41.7g of urea, and use the filtrate to make the volume to 4L, the solution concentration is K2O125g / L, and the solution pH value is 9.5, as a precipitant; weigh 2.3g of zirconium nitrate, 0.97g of lanthanum nitrate, and 1.1g of copper nitrate and dissolve them in 60g of deionized water to prepare a modified auxiliary agent solution.
[0113] First, add deionized water to the reactor, preheat it to 60°C, add 1L aluminum nitrate solution and 1.5L potassium carbonate solution in parallel under stirring, adjust the flow rate of solution addition, control the pH value of the slurry in the reactor to 7, and add the feed time for 40min; after the addition is completed, continue to add the mixed modification auxiliary solution of zirconium nitrate and lanthanum nitrate and 152mL potassium carbonate solution in parallel under stirring, adjust the flow rate of solution addition, and add the feed time for 5min; after the addition is completed, stand and age for 120min at this temperature and pH value. After the aging is completed, filter and dry the obtained filter cake at 150°C for 120min to obtain modified alumina dry glue.
[0114] Example 1
[0115] Weigh 374g of aluminum nitrate nonahydrate and dissolve it in the filtrate, adjust the volume to 1L, and the solution concentration Al2O3 is 51g / L; weigh 706g of potassium carbonate and dissolve it in the filtrate, add 26.8g of urea, and use the filtrate to adjust the volume to 4L, the solution concentration K2O is 125g / L, and the solution pH is 8, as a precipitant; weigh 2.3g of zirconium nitrate, 0.97g of lanthanum nitrate, and 1.1g of copper nitrate and dissolve them in 60g of deionized water to prepare a modification additive solution.
[0116] First add the filtrate to the reactor, preheat to 60°C, add 1L aluminum nitrate solution and 1.62L potassium carbonate solution in parallel under stirring, adjust the flow rate of solution addition, control the pH value of the slurry in the reactor to 7, and add the feeding time to 40min; after the addition is completed, continue to add the mixed modification auxiliary solution of zirconium nitrate and lanthanum nitrate and 165mL potassium carbonate solution in parallel under stirring, adjust the flow rate of solution addition, and add the feeding time to 5min; after the addition is completed, stand and age for 120min at this temperature and pH value. After the aging is completed, add 12g of alumina dry glue prepared in this application as a structure directing agent to the slurry, add it to the high-pressure reactor after stirring, crystallize it at 120°C for 360min, and then filter it. The obtained filter cake is dried at 150°C for 120min, and the filtrate is recycled as a dissolving solution of aluminum salt and potassium carbonate.
[0117] Preparation of carrier: Weigh 100g filter cake (dry basis 71%), 2.1g sesbania powder, and 1.3g methyl cellulose into a kneader and knead for 10 minutes; add 2.5g silica sol, 2.1g acetic acid, and 1.4g citric acid in turn into 60g deionized water and stir until dissolved. Slowly add the obtained solution into the kneader and knead for 30 minutes. The mixed material is extruded, dried at 120°C, and calcined at 550°C for 4 hours to obtain carrier Z1.
[0118] Catalyst preparation: Weigh 8.0 g of ammonium heptamolybdate, 2.0 g of citric acid, and 1.0 g of nitrilotriacetic acid, dissolve in deionized water, stir evenly to obtain a clear solution, add 6.9 g of cobalt nitrate and stir until dissolved, dilute to 42 mL with deionized water, and the pH value is 2.0-3.0; weigh 50 g of carrier Z1 for equal volume impregnation, vacuum impregnation pressure 0.08 MPa, stand for 6 hours, dry at 120°C for 4 hours, and calcine at 500°C for 4 hours to obtain catalyst A1.
[0119] Example 2
[0120] Weigh 374g aluminum nitrate nonahydrate and dissolve it in the filtrate, dilute to 1L, and the solution concentration Al2O3 is 51g / L; weigh 706g potassium carbonate and dissolve it in the filtrate, add 41.7g urea, and dilute to 4L with the filtrate, the solution concentration K2O is 125g / L, and the solution pH is 9.5, as a precipitant; weigh 2.3g zirconium nitrate, 0.97g lanthanum nitrate, and 1.1g copper nitrate and dissolve them in 60g deionized water to prepare a modification additive solution. The pH value of the slurry in the reactor is controlled to 8, and the other steps are the same as Example 1.
[0121] The preparation method of carrier Z2 is the same as that of carrier Z1, except that 2.5 g silica sol, 2.3 g acetic acid and 1.4 g citric acid are added to 62 g deionized water in sequence, followed by mixing, extruding, drying and calcining. The XRD spectrum is shown in Figure 1 ,from Figure 1It can be seen that the typical γ-Al2O3 characteristic diffraction peaks appearing at diffraction angles 2θ of 36.8°, 46.4° and 67.0° have sharp peak shapes and high peak intensities, indicating that the modified alumina carrier prepared in Example 2 has relatively complete crystallization and high crystallinity.
[0122] The metal impregnation method of catalyst A2 is the same as that of A1, with the only difference being that the volume is fixed to 41 mL with deionized water, followed by impregnation, drying, and calcination to obtain catalyst A2.
[0123] Example 3
[0124] Weigh 374g aluminum nitrate nonahydrate and dissolve it in the filtrate, adjust the volume to 1L, and the solution concentration Al2O3 is 51g / L; weigh 706g potassium carbonate and dissolve it in the filtrate, add 41.1g urea and 15.6g ammonia water, and use the filtrate to adjust the volume to 4L, the solution concentration K2O is 125g / L, and the solution pH is 11, as a precipitant; weigh 2.3g zirconium nitrate, 0.97g lanthanum nitrate, and 1.1g copper nitrate and dissolve them in 60g deionized water to prepare a modification additive solution. The pH value of the slurry in the reactor is controlled to 9, and the other steps are the same as Example 1.
[0125] The preparation method of carrier Z3 is the same as that of carrier Z1, except that 2.5 g of silica sol, 2.4 g of acetic acid and 1.5 g of citric acid are added to 61 g of deionized water in sequence, followed by mixing, kneading, extruding, drying and calcining.
[0126] The metal impregnation method of catalyst A3 is the same as that of A1, the only difference is that the volume is fixed to 39 ml with deionized water, and then impregnation, drying and calcination are carried out to obtain catalyst A3.
[0127] Example 4
[0128] The method of Example 2 was followed, except that 6 g of the alumina dry glue prepared in this example was added and crystallized at 150° C. for 360 min.
[0129] The preparation method of carrier Z4 is the same as that of carrier Z2, the only difference being that 2.5 g of silica sol, 2.2 g of acetic acid and 1.4 g of citric acid are sequentially added into 61 g of deionized water, followed by mixing, kneading, extruding, drying and calcining.
[0130] The metal impregnation method of catalyst A4 is the same as that of A2, the only difference being that the volume is fixed to 42 mL with deionized water, followed by impregnation, drying, and calcination to obtain catalyst A4.
[0131] Example 5
[0132] The method of Example 4 was followed, except that the crystallization was performed at 180° C. for 300 min.
[0133] The preparation method of carrier Z5 is the same as that of carrier Z4, which is to add 2.5g silica sol, 2.3g acetic acid, and 1.4g citric acid into 62g deionized water in sequence.
[0134] The metal impregnation method of catalyst A5 is the same as that of A4, with the only difference being that the volume is fixed to 41 mL with deionized water, followed by impregnation, drying, and calcination to obtain catalyst A5.
[0135] Example 6
[0136] The method of Example 4 was followed, except that 2 g of alumina dry glue prepared in the present application was added and crystallized at 150° C. for 120 min.
[0137] The preparation method of carrier Z6 is the same as that of carrier Z4, with the only difference being that 2.5 g of silica sol, 2.3 g of acetic acid and 1.4 g of citric acid are sequentially added into 63 g of deionized water, followed by mixing, kneading, extruding, drying and calcining.
[0138] The metal impregnation method of catalyst A6 is the same as that of A4, the only difference is that the volume is fixed to 40 mL with deionized water, and then impregnation, drying and calcination are carried out to obtain catalyst A6.
[0139] Example 7
[0140] Weigh 374g aluminum nitrate nonahydrate and dissolve it in the filtrate, dilute to 1L, and the solution concentration Al2O3 is 51g / L; weigh 706g potassium carbonate and dissolve it in the filtrate, add 41.7g urea, and dilute to 4L with the filtrate, the solution concentration K2O is 125g / L, and the solution pH is 9.5, as a precipitant; weigh 0.5g zirconium nitrate, 0.2g lanthanum nitrate, and 0.2g copper nitrate and dissolve them in 60g deionized water to prepare a modification auxiliary solution. The other steps are the same as Example 4.
[0141] The preparation method of carrier Z7 is the same as that of carrier Z4, the only difference being that 2.5 g of silica sol, 1.9 g of acetic acid and 1.4 g of citric acid are sequentially added into 61 g of deionized water, followed by mixing, kneading, extruding, drying and calcining.
[0142] The metal impregnation method of catalyst A7 is the same as that of A4 to obtain catalyst A7.
[0143] Example 8
[0144] Weigh 374g aluminum nitrate nonahydrate and dissolve it in the filtrate, dilute to 1L, and the solution concentration Al2O3 is 51g / L; weigh 706g potassium carbonate and dissolve it in the filtrate, add 41.7g urea, and dilute to 4L with the filtrate, the solution concentration K2O is 125g / L, and the solution pH is 9.5, as a precipitant; weigh 4.7g zirconium nitrate, 1.9g lanthanum nitrate, and 4.4g copper nitrate and dissolve them in 100g deionized water to prepare a modification auxiliary solution. The other steps are the same as Example 4.
[0145] The preparation method of carrier Z8 is the same as that of carrier Z4 in Example 4, with the only difference being that 2.5 g of silica sol, 2.5 g of acetic acid and 1.4 g of citric acid are sequentially added to 62 g of deionized water, followed by mixing, kneading, extruding, drying and calcining.
[0146] The metal impregnation method of catalyst A8 is the same as that of catalyst A4 in Example 4, with the only difference being that the volume is fixed to 40 mL with deionized water, followed by impregnation, drying and calcination to obtain catalyst A8.
[0147] Example 9
[0148] According to the method of Example 4, 6 g of the alumina dry glue prepared in this example was added and crystallized at 150° C. for 360 min.
[0149] The preparation method of carrier Z9 is the same as that of carrier Z4 in Example 4.
[0150] Weigh 5.5 g of ammonium heptamolybdate, 1.7 g of citric acid, and 1.0 g of nitrilotriacetic acid, dissolve in deionized water, stir evenly to obtain a clear solution, add 2.2 g of cobalt nitrate and stir until dissolved, dilute to 42 mL with deionized water, and the pH value is 2.0-3.0; weigh 50 g of carrier Z9 for equal volume impregnation, vacuum impregnation pressure of 0.08 MPa, stand for 6 hours, dry at 120°C for 4 hours, and calcine at 500°C for 4 hours to obtain catalyst A9.
[0151] Example 10
[0152] According to the method of Example 4, 6 g of the alumina dry glue prepared in this example was added and crystallized at 150° C. for 360 min.
[0153] The preparation method of carrier Z10 is the same as that of carrier Z4 in Example 4.
[0154] The catalyst was prepared by two-step impregnation: first, 7.2 g of ammonium heptamolybdate, 1.8 g of citric acid, and 1.0 g of nitrilotriacetic acid were weighed, dissolved in deionized water, and stirred evenly to obtain a clear solution. Then, 6.8 g of cobalt nitrate was added and stirred until dissolved. The volume was adjusted to 42 mL with deionized water, and the pH value was 2.0-3.0. 50 g of carrier Z10 was weighed for equal volume impregnation, the vacuum impregnation pressure was 0.08 MPa, and the mixture was allowed to stand for 6 hours, dried at 120°C for 4 hours, and calcined at 500°C for 4 hours to obtain a single impregnation catalyst. Weigh 4.0 g of ammonium heptamolybdate, 1.4 g of citric acid, and 0.8 g of nitrilotriacetic acid, dissolve in deionized water, stir evenly to obtain a clear solution, add 2.1 g of cobalt nitrate and stir until dissolved, dilute to 33 mL with deionized water, and the pH value is 2.0-3.0; weigh 50 g of one-step impregnation carrier for equal volume impregnation, vacuum impregnation pressure of 0.08 MPa, stand for 6 hours, dry at 120°C for 4 hours, and calcine at 500°C for 4 hours to obtain catalyst A10.
[0155] Embodiment 11
[0156] The method of Example 1 is followed, except that “the filtrate is first added to the reactor, preheated to 20°C, 1L of aluminum nitrate solution and 1.62L of potassium carbonate solution are added in parallel with stirring, the flow rate of solution addition is adjusted, the pH value of the slurry in the reactor is controlled to be 7, and the feeding time is 50min” is replaced by “the filtrate is first added to the reactor, preheated to 60°C, 1L of aluminum nitrate solution and 1.62L of potassium carbonate solution are added in parallel with stirring, the flow rate of solution addition is adjusted, the pH value of the slurry in the reactor is controlled to be 7, and the feeding time is 40min”.
[0157] The preparation of the carrier and the catalyst was the same as in Example 1 to obtain catalyst A11.
[0158] Example 12
[0159] The method of Example 11 is followed, except that “Under stirring conditions, continue to add the mixed modification auxiliary solution of zirconium nitrate and lanthanum nitrate and 165 mL of potassium carbonate solution in parallel, adjust the solution addition flow rate, and add the feeding time for 10 min” is replaced by “Under stirring conditions, continue to add the mixed modification auxiliary solution of zirconium nitrate and lanthanum nitrate and 165 mL of potassium carbonate solution in parallel, adjust the solution addition flow rate, and add the feeding time for 5 min”.
[0160] The preparation of the carrier and the catalyst was the same as in Example 1 to obtain catalyst A12.
[0161] Comparative Example 1
[0162] Weigh 374g of aluminum nitrate nonahydrate and dissolve it in deionized water, dilute to 1L, and the solution concentration of Al2O3 is 51g / L; weigh 830g of potassium carbonate and dissolve it in deionized water, dilute to 4.0L, and the solution concentration of K2O is 142g / L as a precipitant; weigh 2.3g of zirconium nitrate, 0.97g of lanthanum nitrate, and 1.1g of copper nitrate and dissolve them in 100g of deionized water to prepare a modified auxiliary solution. First add bottom water to the reactor, preheat it to 60°C, add aluminum nitrate solution and potassium carbonate solution in parallel under stirring, adjust the flow rate of solution addition, control the pH value of the slurry in the reactor to 8, and the feeding time is 40min; after the addition is completed, continue to add the mixed modified auxiliary solution of zirconium nitrate and lanthanum nitrate and potassium carbonate solution in parallel under stirring conditions, adjust the flow rate of solution addition, and the feeding time is 6min; after the addition is completed, stand and age for 120min at this temperature and pH value. After aging, the slurry was filtered and the filter cake was washed with deionized water several times to remove the precipitant metal cation K + , wash until the filtrate is neutral, and dry the filter cake at 150℃ for 120min.
[0163] 100 g of filter cake (dry basis 71%), 2.1 g of sesbania powder, and 1.4 g of methyl cellulose were weighed and added to a kneader and kneaded for 10 min; 2.5 g of silica sol, 1.9 g of acetic acid, and 1.4 g of citric acid were added to 60 g of deionized water in sequence and stirred until dissolved. The resulting solution was slowly added to the kneader and kneaded for 30 min. The mixed material was extruded, dried at 120 ° C, and calcined at 550 ° C for 4 hours to obtain a carrier DZ1. The XRD spectrum is shown in Figure 2 ,from Figure 2 It can be seen that the typical γ-Al2O3 characteristic diffraction peaks appearing at diffraction angles 2θ of 36.8°, 46.4° and 67.0° have broad peak shapes and low peak intensities, especially the 36.8° characteristic diffraction peak, which indicates that the modified alumina carrier prepared in Comparative Example 1 has incomplete crystallization and low crystallinity.
[0164] Weigh 8.0 g of ammonium heptamolybdate, 2.0 g of citric acid, and 1.0 g of nitrilotriacetic acid, dissolve in deionized water, stir evenly to obtain a clear solution, add 6.9 g of cobalt nitrate and stir until dissolved, dilute to 40 mL with deionized water, and the pH value is 2.0-3.0; weigh 50 g of carrier Z1 for equal volume impregnation, vacuum impregnation pressure of 0.08 MPa, stand for 6 hours, dry at 120°C for 4 hours, and calcine at 500°C for 4 hours to obtain catalyst D1.
[0165] Comparative Example 2
[0166] Take 374g of aluminum nitrate nonahydrate and dissolve it in the filtrate, adjust the volume to 1L, and the solution concentration Al2O3 is 51g / L; weigh 706g of potassium carbonate and dissolve it in the filtrate, add 45.1g of urea and 36g of ammonia water, and use the filtrate to adjust the volume to 4L, the solution concentration K2O is 125g / L, and the solution pH is 12, as a precipitant; weigh 2.3g of zirconium nitrate, 0.97g of lanthanum nitrate, and 1.1g of copper nitrate and dissolve them in 60g of deionized water to prepare a modification aid solution. Add the aluminum nitrate solution, the modification aid solution and the potassium carbonate solution to the reactor in parallel, and control the pH value of the slurry in the reactor to be 10, and the rest is the same as Example 4.
[0167] The method for carrier DZ2 is the same as that for carrier Z4 in Example 4, except that 2.5 g of silica sol, 2.5 g of acetic acid and 1.4 g of citric acid are added to 61 g of deionized water in sequence, followed by mixing, kneading, extruding, drying and calcining.
[0168] The metal impregnation method of catalyst D2 is the same as that of catalyst A4 in Example 4, with the only difference being that the volume is fixed to 39 mL with deionized water, followed by impregnation, drying and calcination to obtain catalyst D2.
[0169] Comparative Example 3
[0170] The method of Example 1 is followed, except that "the filtrate is first added to the reactor, preheated to 60°C, 1L of aluminum nitrate solution and 1.62L of potassium carbonate solution are added in parallel under stirring, 12g of alumina dry gel prepared in the present application is added as a structure directing agent, the flow rate of solution addition is regulated, the pH value of the slurry in the reactor is controlled to be 7, and the feeding time is 40min. After the addition is completed, a mixed modification auxiliary solution of zirconium nitrate and lanthanum nitrate and 165mL of potassium carbonate solution are added in parallel under stirring, the flow rate of solution addition is regulated, and the feeding time is 5min. After the addition is completed, the mixture is allowed to stand and age for 120min at this temperature and pH value. After the aging is completed, the mixture is added to the autoclave after being stirred evenly, crystallized at 120°C for 360min, and then filtered. The filter cake obtained is dried at 150°C for 120min, and the filtrate is recycled as a dissolving solution of aluminum salt and potassium carbonate."
[0171] replace
[0172] "First, add the filtrate to the reactor, preheat it to 60°C, add 1L aluminum nitrate solution and 1.62L potassium carbonate solution in parallel under stirring, adjust the flow rate of solution addition, control the pH value of the slurry in the reactor to 7, and add the feeding time for 40min; after the addition is completed, continue to add the mixed modification auxiliary solution of zirconium nitrate and lanthanum nitrate and 165mL potassium carbonate solution in parallel under stirring conditions, adjust the flow rate of solution addition, and add the feeding time for 5min; after the addition is completed, stand and age for 120min at this temperature and pH value. After the aging is completed, add 12g of alumina dry glue prepared in this application as a structure directing agent to the slurry, add it to the high-pressure reactor after stirring, crystallize it at 120°C for 360min, and then filter it. The obtained filter cake is dried at 150°C for 120min, and the filtrate is recycled as a dissolving solution of aluminum salt and potassium carbonate."
[0173] The preparation of the carrier and the catalyst was the same as in Example 1 to obtain catalyst D3.
[0174] Comparative Example 4
[0175] The method of Example 1 was followed, except that in the carrier preparation step, "100 g of filter cake (71% on dry basis) and 2.1 g of sesbania powder were weighed and added to a kneader and kneaded for 10 min; 2.5 g of silica sol and 2.1 g of acetic acid were added to 60 g of deionized water in sequence and stirred until dissolved, and the obtained solution was slowly added to a kneader and kneaded for 30 min, and the mixed material was extruded, dried at 120° C., and calcined at 550° C. for 4 hours to obtain carrier D4." was replaced by "100 g of filter cake (71% on dry basis), 2.1 g of sesbania powder and 1.3 g of methyl cellulose were weighed and added to a kneader and kneaded for 10 min; 2.5 g of silica sol, 2.1 g of acetic acid and 1.4 g of citric acid were added to 60 g of deionized water in sequence and stirred until dissolved, and the obtained solution was slowly added to a kneader and kneaded for 30 min, and the mixed material was extruded, dried at 120° C., and calcined at 550° C. for 4 hours to obtain carrier Z1."
[0176] The other steps were the same as those in Example 1 to obtain catalyst D4.
[0177] The main properties of the modified alumina supports prepared in Examples 1-12 and Comparative Examples 1-4 are shown in Table 1.
[0178] The main properties of the hydrodesulfurization catalysts prepared in Examples 1-12 and Comparative Examples 1-4 are shown in Table 2.
[0179] The hydrodesulfurization catalysts prepared in Examples 1-12 and Comparative Examples 1-4 were respectively loaded into a 100 mL hydrogenation evaluation device for performance evaluation. The catalyst was wet-sulfurized, the sulfurizing agent was carbon disulfide, the sulfurized oil was refined naphtha, and hydrogen was passed once. The sulfurization conditions were: 150°C for sulfurized oil, staying for 2h; heating to 230°C at a heating rate of 20-30°C / h, staying for 8h; continuing to heat to 320°C at a heating rate of 20-30°C / h, staying for 6h; the volume space velocity was 2h -1 The hydrogen-to-oil ratio is 200:1 and the pressure is 2.0MPa; after the sulfurization is completed, the temperature is lowered to 230°C and the catalytic heavy gasoline raw material is replaced.
[0180] Hydrogenation reaction conditions: reaction temperature 260°C, reaction pressure 2.0 MPa, hydrogen-oil volume ratio 300:1, volume space velocity 2.5 h -1 The properties of heavy gasoline feedstock and hydrogenation products are shown in Table 3.
[0181] Table 1 Physical and chemical properties of modified alumina support
[0182]
[0183] Note: Composition % is weight %.
[0184] Table 1 (continued)
[0185]
[0186] Table 1 (continued)
[0187]
[0188]
[0189] Table 2 Physicochemical properties of hydrodesulfurization catalyst
[0190] catalyst A1 A2 A3 A4 A5 A6 <![CDATA[Al2O3,%]]> 80.2 79.8 79.3 79.8 80.1 80.3 <![CDATA[MoO3,%]]> 11.1 11.0 11.1 11.1 11.1 11.1 CoO, % 3.0 3.1 3.0 3.0 3.0 3.0 <![CDATA[K2O,%]]> 2.5 2.9 3.5 2.9 2.7 2.6 <![CDATA[ZrO2,%]]> 1.1 1.1 1.0 1.1 1.1 1.0 <![CDATA[La2O3,%]]> 0.6 0.6 0.6 0.6 0.5 0.6 CuO, % 0.6 0.6 0.6 0.6 0.6 0.5 <![CDATA[SiO2,%]]> 0.9 0.9 0.9 0.9 0.9 0.9 <![CDATA[Specific surface area, m 2 / g]]> 223 211 214 219 205 203 <![CDATA[Pore volume, cm 3 / g]]> 0.56 0.51 0.45 0.52 0.50 0.48 10-20nm pore size, % 63 75 66 82 65 64 <![CDATA[K2O content in catalyst unloading, %]]> 2.4 2.9 3.5 2.9 2.6 2.6
[0191] Note: Composition % is weight %.
[0192] Table 2 (continued)
[0193]
[0194]
[0195] Table 2 (continued)
[0196] catalyst D1 D2 D3 D4 <![CDATA[Al2O3,%]]> 82.2 78.4 80.2 80.2 <![CDATA[MoO3,%]]> 11.1 11.0 11.1 11.1 CoO, % 3.0 3.0 3.0 3.0 <![CDATA[K2O,%]]> 0.3 4.4 2.5 2.5 <![CDATA[ZrO2,%]]> 1.3 1.1 1.1 1.1 <![CDATA[La2O3,%]]> 0.6 0.6 0.6 0.6 CuO, % 0.6 0.6 0.6 0.6 <![CDATA[SiO2,%]]> 0.9 0.9 0.9 0.9 <![CDATA[Specific surface area, m 2 / g]]> 191 189 202 208 <![CDATA[Pore volume, cm 3 / g]]> 0.47 0.44 0.46 0.41 10-20nm pore size, % 36 51 59 50 <![CDATA[K2O content in catalyst discharging, %]]> 0.1 4.3 2.4 2.4
[0197] Table 3 Raw oil and product properties
[0198]
[0199] Table 3 (continued)
[0200]
[0201]
[0202] Table 3 (continued)
[0203]
[0204] Comparing the evaluation data in Table 3, it can be seen that the desulfurization activity and selectivity of the hydroprocessing catalyst prepared by the method of the present invention are significantly better than those of the catalyst prepared by the conventional method of the prior art in the selective desulfurization process, and the purpose of highly selective deep desulfurization of clean gasoline of the National VI standard is achieved while reducing octane number loss.
[0205] Among them, Examples 2, 4, 5, and 6 achieve the modification of the alumina crystal structure, crystallinity, and pore structure by adjusting the hydrothermal crystallization temperature, crystallization time, and the proportion of alumina dry glue added, promote the regular formation and growth of crystal nuclei, improve the modified alumina crystallinity and crystal structure integrity and the formation of metal additive-O-Al bonds, adjust the interaction force between the carrier and the active metal component, and promote the formation of MoS2 active phase. Examples 1-3 achieve the modulation of K content and the modification of pore structure by adjusting the pH value of the precipitant, the pH value of the precipitation reaction, and introducing the hydrothermal crystallization method; Examples 4, 7, and 8 achieve the modification of pore structure and the regulation of the interaction force between metal and carrier by adjusting the content of the modified additive; Examples 4, 9, and 10 achieve the regulation of active phase structure by adjusting the content of metal active components. In Example 11 and Example 12, the temperature and time of the first precipitation and the second precipitation are adjusted, so that the precipitation reaction depth is regulated at different temperatures to achieve the modulation of the pore structure; at the same time, the catalyst prepared in Examples 1-12 is used to treat catalytic heavy gasoline. After a certain period of operation, the potassium content of the catalyst discharged is basically equivalent to that of the fresh catalyst, indicating that there is no potassium loss during the operation.
[0206] Among them, compared with the embodiment, comparative example 1 adds multiple washing of the filter cake to remove K + In the process, in addition to the disadvantage of generating a large amount of waste liquid that is not conducive to environmental protection, the prepared catalyst lacks the modification effect of the modification agent K and the 10-20nm pore ratio is low, resulting in a significant decrease in the desulfurization activity and selectivity of the catalyst; Compared with the embodiment, the pH value of the filter cake preparation process in Comparative Example 2 is 10. A higher pH value easily leads to a higher K content on the catalyst and a lower 10-20nm pore ratio, which is not conducive to the effective utilization of the active components, resulting in a decrease in the desulfurization activity and selectivity of the catalyst.
[0207] Among them, by comparing Example 1 with Comparative Example 3, it can be seen that adjusting the timing of adding the "structure directing agent" can fully exert the effect of the structure directing agent in the crystallization process, promote the regular formation and growth of crystal nuclei, and significantly improve the crystallinity.
[0208] Among them, by comparing Example 1 and Comparative Example 4, it can be seen that the addition of a "pore expander" in Example 1 can obtain a modified alumina carrier with a larger average pore size, thereby increasing the proportion of catalysts with a pore size of 10-20 nm, which helps to improve the desulfurization selectivity of the catalyst.
[0209] The present invention adopts a method in which potassium salt is used as both a precipitant and a precursor of a modified metal additive during the carrier preparation process, and the metal additive is prompted to enter the pores of alumina through in-situ modification of potassium, thereby eliminating the need for the filter cake to be washed multiple times to remove potassium. + The steps of the invention simplify the production process and solve the problem of easy loss of the modification auxiliary agent during the use of the catalyst. At the same time, the co-precipitation slurry hydrothermal crystallization method is combined to further improve the crystallinity of the modified alumina carrier, promote the integrity of the crystal structure and the formation of metal auxiliary agent-O-Al bonds, obtain a modified alumina carrier with a concentrated pore structure, reduce the number of surface hydroxyl groups, and achieve precise control of the metal active phase. The filtrate recycling method is adopted, and the solution obtained after filtration is used as a solvent for dissolving aluminum salts and alkaline precipitants. By adjusting the pH value of the precipitant solution, the required pH value environment in the precipitation process is achieved, and sufficient precipitation is achieved. At the same time, the environmentally friendly production problem of zero emission of waste liquid containing metal ions is solved. The catalyst shows excellent desulfurization activity and selectivity, which meets the needs of deep desulfurization and reduction of octane number loss in the process of upgrading the quality of clean gasoline to the National VI standard.
[0210] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A modified alumina carrier, characterized in that: The modified alumina carrier comprises silicon oxide, potassium oxide, zirconium oxide, lanthanum oxide, copper oxide and aluminum oxide; The volume percentage of pores with a pore diameter of 13-23 nm accounts for 63-85% of the total pore volume, and the relative crystallinity is not less than 95%.
2. The modified alumina carrier according to claim 1, characterized in that The specific surface area of the modified alumina carrier is 230-260m 2 / g, pore volume is 0.5-1.1mL / g, and average pore diameter is 12-22nm; Preferably, the specific surface area of the modified alumina carrier is 233-255m 2 / g, pore volume is 0.6-1mL / g, and average pore diameter is 13-18nm; Preferably, the volume percentage of pores with a pore diameter of 14-19 nm to the total pore volume is 60-80%, and the relative crystallinity is not less than 95%.
3. The modified alumina carrier according to claim 1 or 2, characterized in that: Based on the total weight of the modified alumina carrier, the content of silicon oxide is 0.1-1.5wt%, the content of potassium oxide is 2-4.5wt%, the content of zirconium oxide is 0.1-2.3wt%, the content of lanthanum oxide is 0.1-1.3wt%, the content of copper oxide is 0.1-2.3wt%, and the content of aluminum oxide is 88.1-97.6wt%; Preferably, based on the total weight of the modified alumina carrier, the content of silicon oxide is 0.5-1.1wt%, the content of potassium oxide is 2.5-4.1wt%, the content of zirconium oxide is 0.5-1.5wt%, the content of lanthanum oxide is 0.3-0.8wt%, the content of copper oxide is 0.3-0.8wt%, and the content of aluminum oxide is 91.7-95.9wt%.
4. A method for preparing a modified alumina carrier, characterized in that: The following steps are involved: (1) subjecting an alkaline precipitant solution, an aluminum salt solution and a modified metal salt solution to a precipitation reaction, and subjecting the obtained product to an aging reaction; (2) subjecting the slurry obtained in step (1) to a hydrothermal crystallization reaction with a structure directing agent and filtering; (3) The filter cake obtained by filtering in step (2) is molded with a binder, a pore-enlarging agent and an extrusion aid to obtain a modified alumina carrier.
5. The method according to claim 4, characterized in that The alkaline precipitant solution in step (1) comprises an alkaline precipitant, and the alkaline precipitant is selected from one or more of potassium carbonate, potassium hydroxide and potassium bicarbonate; The aluminum salt solution comprises a soluble aluminum salt, and the soluble aluminum salt is selected from aluminum nitrate and / or aluminum sulfate; The modified metal salt solution contains modified metal salt, and the modified metal salt is selected from one or more of zirconium nitrate, lanthanum nitrate, copper nitrate, zirconium acetate, lanthanum acetate, and copper acetate.
6. The method according to claim 4 or 5, characterized in that: The precipitation reaction in step (1) includes a first precipitation reaction of the alkaline precipitant solution and an aluminum salt solution, and a second precipitation reaction of the alkaline precipitant solution and a modified metal salt solution; The conditions of the first precipitation reaction include: reaction temperature of 20-80°C, pH of 7-9, and reaction time of 30-50 min; preferably, reaction temperature of 50-70°C, pH of 8-9, and reaction time of 30-40 min; The conditions of the second precipitation reaction include: reaction temperature of 20-80°C, pH of 7-9, and reaction time of 3-10 min; preferably, reaction temperature of 50-70°C, pH of 8-9, and reaction time of 5-8 min.
7. The method according to claim 4, characterized in that The structure directing agent in step (2) is modified alumina dry glue; Preferably, the mass ratio of the structure directing agent to the slurry is 0.0012-0.0046:
1.
8. The method according to claim 4, characterized in that The conditions of the hydrothermal crystallization reaction in step (2) include: a reaction temperature of 120-180° C. and a reaction time of 120-600 min; Preferably, the reaction temperature is 130-160° C., and the reaction time is 180-360 min.
9. The method according to claim 4, characterized in that The binder in step (3) comprises silica sol and compound A, wherein the compound A is selected from one or more of nitric acid, acetic acid and malic acid; The pore expanding agent is selected from one or more of citric acid, yeast, methyl cellulose, and hydroxypropyl methyl cellulose; The extrusion aid is selected from one or more of sesbania powder, starch and citric acid.
10. The method according to claim 4, characterized in that The mass ratio of the filter cake, the binder, the pore expanding agent and the extrusion aid in step (3) is 1:0.02-0.05:0.01-0.1:0.01-0.
05.
11. A modified alumina carrier prepared according to the method according to any one of claims 4 to 10.
12. A hydrodesulfurization catalyst, characterized in that: The catalyst comprises a carrier and an active component A and an active component B supported on the carrier, wherein the carrier is selected from the carrier according to any one of claims 1 to 3 and 11; Wherein, the active component A includes cobalt oxide and / or nickel oxide; the active component B is molybdenum oxide; Wherein, based on the total weight of the catalyst, the content of the active component A is 1-4wt%, the content of the active component B is 8-16wt%, and the content of the carrier is 80-91wt%.
13. Use of the catalyst according to claim 12 in the selective hydrodesulfurization of catalytic cracking gasoline.
14. A method for selective hydrodesulfurization of catalytic cracking gasoline, the method comprising: The catalyst according to claim 12 is subjected to a presulfurization treatment, and the obtained presulfurized catalyst is contacted with catalytic cracking gasoline to carry out a selective hydrodesulfurization reaction.
Citation Information
Patent Citations
Medium-oil-type hydrocracking catalyst and preparation method thereof
CN106669779A
Modified pseudo-boehmite, preparation method thereof, modified alumina and hydrogenation catalyst
CN113562751A
Mild Acidic Catalyst for Hydroprocessing of Heavy Crude Oil and Residue and its Synthesis Procedure
US20110100875A1